The Relationship Between Team Size, Location, and Performance in Preclinical Medical Education Active Learning - Ashley M. Tuin; Thomas Schechter; Kenneth A.D. Palattao; Cassandra Hays; Kenneth L. Kramer; Cassie A. Eno (Journal of Medical Education and Curricular Development)
Background Case-based learning (CBL) and team-based learning (TBL) in preclerkship medical education are popular learning methods. Our institution utilizes a novel approach of using CBL as prework for TBL. Research has shown that smaller group sizes are better for CBL, whereas larger group sizes are better for TBL. Further, the spatial relationship of students in classrooms and subsequent academic performance has been studied previously but has not yet explored the medical student population during active learning methods. We investigated the effect of group size in active learning, classroom location, and subsequent performance on TBL and final exam questions. Methods Student performance data from 4 preclerkship medical cohorts were analyzed. Descriptive statistics was conducted to compare performance of each cohort. Regression analysis was conducted to determine the explanatory and predictive power of group size and location on individual and team TBL performance and exam performance. Results Larger groups had increased individual and team performance on TBL. Classroom location had mixed effects on TBL and exam performance. One cohort experienced a change in group sizes and learning environment which may be related to the lower TBL scores compared to other cohorts. We found no significant relationships between group size and exam scores. Conclusions Our findings indicate that larger groups are associated with increased TBL performance. Exam scores are more likely impacted by individual factors, as opposed to group factors. Our findings were mixed in comparison to previous research, reaffirming the need to further study group sizes and locations specifically within the health science education active learning.